Betel Leaf Decoction Therapy for Accelerating the Healing of Perineal Sutured Wounds among Postpartum Mothers at the Paccing Community Health Center, Bone Regency - Muchtar, Asrianti Safitri; Ita Novianti; Suci Awalia Ramadani (Jurnal Midwifery, 2026)
Introduction: Perineal rupture is an injury to the birth canal that may occur with or without the use of obstetric instruments during childbirth. Factors contributing to perineal rupture include the childbirth process itself, excessive fetal birth weight, improper delivery techniques, perineal rigidity, vacuum extraction, and trauma resulting from perineal incision instruments. In postpartum women, inadequately managed perineal wounds are highly susceptible to infection, which can significantly affect the healing process of the perineal wound. Objective: This study aimed to provide midwifery care to Mrs. “Y” through the administration of betel leaf (Piper betle) decoction therapy to accelerate the healing of perineal suture wounds at the Paccing Primary Health Center, Bone Regency. Methods: This study employed a case study design tailored to the client’s needs and within the scope of midwifery authority, using the seven-step Varney midwifery management approach with documentation in SOAP format. Results: The case study involved Mrs. “Y,” a 28-year-old postpartum woman with a perineal suture wound, who initially complained of pain during movement and discomfort while performing daily activities. After three days of midwifery care, the mother’s general condition was good, consciousness was compos mentis, and vital signs were within normal limits. The mother no longer experienced pain, and the perineal suture wound had healed. Conclusion: The results of the midwifery care provided indicate that betel leaf decoction therapy was effective in accelerating the healing of perineal wounds in Mrs. “Y.”